Impact of Starch Binding Domain Fusion on Activities and Starch Product Structure of 4-α-Glucanotransferase - Yu Wang; Yazhen Wu; Stefan Jarl Christensen; Štefan Janeček; Yuxiang Bai; Marie Sofie Møller; Birte Svensson (Molecules, 2023)
A broad range of enzymes are used to modify starch for various applications. Here, a thermophilic 4-α-glucanotransferase from Thermoproteus uzoniensis (TuαGT) is engineered by N-terminal fusion of the starch binding domains (SBDs) of carbohydrate binding module family 20 (CBM20) to enhance its affinity for granular starch. The SBDs are N-terminal tandem domains (SBDSt1 and SBDSt2) from Solanum tuberosum disproportionating enzyme 2 (StDPE2) and the C-terminal domain (SBDGA) of glucoamylase from Aspergillus niger (AnGA). In silico analysis of CBM20s revealed that SBDGA and copies one and two of GH77 DPE2s belong to well separated clusters in the evolutionary tree; the second copies being more closely related to non-CAZyme CBM20s. The activity of SBD-TuαGT fusions increased 1.2–2.4-fold on amylose and decreased 3–9 fold on maltotriose compared with TuαGT. The fusions showed similar disproportionation activity on gelatinised normal maize starch (NMS). Notably, hydrolytic activity was 1.3–1.7-fold elevated for the fusions leading to a reduced molecule weight and higher α-1,6/α-1,4-linkage ratio of the modified starch. Notably, SBDGA-TuαGT and-SBDSt2-TuαGT showed Kd of 0.7 and 1.5 mg/mL for waxy maize starch (WMS) granules, whereas TuαGT and SBDSt1-TuαGT had 3–5-fold lower affinity. SBDSt2 contributed more than SBDSt1 to activity, substrate binding, and the stability of TuαGT fusions.